Death, diamonds, and deception - Simpson, Rosemary, 1942- (Simpson, Rosemary, 1942- Gilded Age mystery., 2020)
When her sharp-eyed aunt declares a spectacular Marie Antoinette heirloom necklace a counterfeit, Prudence and her partner, Geoffrey, trace the necklace's stolen diamonds to a jeweler's murder and a banking family's dangerous secrets.